Synthesis and Characterisation of Some Heteropoly Oxomolybdates - KR. ACHARYA, ASHOK (Asian Journal of Chemistry, 2010)
In present studies, some new heteropoly oxomolybdates have been prepared. Rigid physico-chemical condition for the preparation of each hetero poly complexes have been established separately by studying pH measurement. Chemical method for analysis of the compounds have been corroborated by colorimetric and flame photometric analysis. Weissenberg's X-ray crystal diffraction technique has been successfully applied to determine the actual molecular weights of some crystalline compounds. Nature of bonds and water molecules was characterized by TG, DTA and IR analysis.